Νεοελληνική ιστοριογραφία. - Φωτιάδης, Ευάγγελος Π., 1909-1972 (Βασική βιβλιοθήκη / Αετός, 1954)
Σπυρίδων, Τρικούπης -- Ανδρέας Μουστοξύδης -- Σπυρίδων Ζαμπέλιος -- Παύλος Καλλιγάς -- Ιωάννης Φιλήμων -- Δημήτριος Ν. Βερναρδάκης -- Διονύσιος Θερειανός -- Μάρκος Ρενιέρης -- Παύλος Καρολίδης -- Αναστάσιος Βυζαντινός -- Αλέξανδρος Βυζάντιος -- Σπυρίδων Λάμπρος -- Γεώργιος Χατζιδάκης -- Αντώνιος Μομφερράτος -- Δημήτριος Βικέλας -- Γιάννης Βλαχογιάννης -- Αδαμάντιος Αδαμαντίου